Barbitürik Asit Halkası İçeren Metakrilat Polimerlerinin Dielektrik Ölçümleri - Çakmak, İdris; Torğut, Gülben (Fırat University, 2016)
Bu çalışmada, farklı oranlarda dietoksikarbonil metilmetakrilat ve barbitürük halkası içeren metakrilat homopolimerleri ve stirenle kopolimerleri hazırlandı. Dielektrik davranışları (dielektrik sabiti ve dielektrik kayıp faktörü) impedans analizör ile ölçüldü. Bu değerler frekansa ve sıcaklığa karşı grafiğe geçirildi ve sonuçlar birbirleriyle karşılaştırıldı. Bütün polimerler için frekans arttıkça dielektrik sabitinin azaldığı yüksek frekanslarda ise sabit kaldığı görüldü. Sentezlenen polimerlerin CuBr ve FeCl3 ile doplanmıs yapılarının da 1 kHz’de farklı sıcaklıklarda da dielektrik özellikler araştırıldı.

In this study, methacrylate homopolymers and copolymers with styrene and methyl methacrylate containing diethoxycarbonyl barbituric ring in different ratios was synthesized according to the literature [1] and was characterized. Dielectric behaviors (dielectric constant and dielectric loss factor) were investigated by impedance analyzer. These values were plotted against frequency and temperature, and the results were compared. Dielectric constant decreases with increasing the frequency and remains constant at high frequencies for all polymers. Dielectric properties was measured of the polymers doped with CuBr and FeCl3 by temperature at 1kHz.
The Dielectric Measurements Of Methacrylate Polymers Containing The Barbituric Acid Ring